Determination of Total Levels of Secondary Metabolites and Oral Acute Toxicity Testing of Purple Leaf Ethanol Extract (PLEE) in Wistar Rats - Niluh Puspita Dewi; Miranti Miranti; Magfirah Magfirah; Athia Kurnia Kasim; I Made Dipayana (Journal of Public Health and Pharmacy)
Introduction: The use of traditional medicines derived from the active ingredients of several types of plants is preferred by the community in treating several types of diseases. One of the plants that has been used by the community as medicine is purple leaves with the Latin name Grapthophylum pictum (L.) Griff. These leaves are traditionally used to treat rheumatism, menstruation, hemorrhoids, urinary tract infections, scabies, swelling, wounds, dermatitis, ear diseases, laxatives, and cancer. The aim of this study was to determine the total levels of secondary metabolites from purple leaf extract ethanol (PLEE) and evaluate the effect of administering PLEE on acute toxicity (LD50) in Wistar rats.